Test-based accountability, standardized testing and minority/racialized students' perspectives in urban schools in Canada and Australia. Issue 5 (3rd September 2021) - Rezai-Rashti, Goli M.; Lingard, Bob
ABSTRACT: This paper focuses on the perspectives of minority/racialized students in urban high schools. It is based on findings of interviews with 85 students in six secondary schools in Toronto and Vancouver, Canada, and in Melbourne, Australia, during 2016–2019. While there has been increasing attention to closing the racial achievement gap and some minority students' underachievement in education, there are limited studies that centre the voices of students and their experiences with provincial and nationally mandated testing. This paper is not an investigation into minority students' achievement; rather it seeks to understand how minority students perceive and experience this new form of test-based accountability. Grounding the analysis within theories of policy sociology and neoliberal accountability, this paper concludes that current policies of standardized testing have catalysed further inequities and segregation of students based on their 'race' and social class.